2008
DOI: 10.1523/jneurosci.3995-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α Mediates Lipopolysaccharide-Induced Microglial Toxicity to Developing Oligodendrocytes When Astrocytes Are Present

Abstract: Reactive microglia and astrocytes are present in lesions of white matter disorders, such as periventricular leukomalacia and multiple sclerosis. However, it is not clear whether they are actively involved in the pathogenesis of these disorders. Previous studies demonstrated that microglia, but not astrocytes, are required for lipopolysaccharide (LPS)-induced selective killing of developing oligodendrocytes (preOLs) and that the toxicity is mediated by microglia-derived peroxynitrite. Here we report that, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 65 publications
7
114
0
Order By: Relevance
“…These findings are consistent with animal studies demonstrating that the up-regulation of cytokines is related to sickness-like behavioural symptoms of anhedonia and dysfunction in cognitive function [6,108] shown by murine studies [6,111]. However, continual exposure to these cytokines results in decreased neurogenesis, apoptosis and cognitive dysfunction [6,67,112].…”
Section: Increase In Peripheral Blood Cytokine Levels Induced By Liposupporting
confidence: 88%
See 2 more Smart Citations
“…These findings are consistent with animal studies demonstrating that the up-regulation of cytokines is related to sickness-like behavioural symptoms of anhedonia and dysfunction in cognitive function [6,108] shown by murine studies [6,111]. However, continual exposure to these cytokines results in decreased neurogenesis, apoptosis and cognitive dysfunction [6,67,112].…”
Section: Increase In Peripheral Blood Cytokine Levels Induced By Liposupporting
confidence: 88%
“…It is synthesized in its pro form as a monomeric type 2 transmembrane protein (tmTNF-α) and is inserted into the cell membrane and cleaved to its soluble form (solTNF-α) by a matrix metalloprotease TNF-α-converting enzyme (TACE/ADAM17) [65]. Both forms of TNF-α are biologically active and are produced in the CNS by astrocytes, microglia as well as neurons [10,66,67].…”
Section: Neurobiology Of Tnf-α In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, taking into account recent observations suggesting that LCN2 alone is not able to induce apoptosis in astrocytes, 26 we cannot discard an indirect modulation of astrocytes' survival by molecules secreted by activated microglia (o5% in astrocyte-enriched cultures), because of their ability to respond to LCN2. 28 In fact, others have shown that in response to LPS, microglia are able to influence the survival of brain cells, oligodendrocytes in particular, by secreting proinflammatory molecules like TNF, 40 and that this process is modulated, in vivo, by LCN2. 28 Of notice, neuronal apoptosis in response to Ab 1-42 is independent of their ability to produce LCN2 as the survival of Lcn2( þ / þ ) and Lcn2( À / À ) neurons significantly decreased in response to Ab .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, peroxynitrite is also responsible for the LPS-induced degeneration of developing oligodendrocytes in coculture experiments (66). However, when astrocytes were present along with oligodendrocytes and microglia, the LPS-induced microglia-dependent toxicity to developing oligodendrocytes was mediated by a mechanism involving TNF-a signaling (67). Thus, in addition to redox-triggered signaling, microgliamediated toxicity is also dependent on a number of immunologically relevant cytokines that can activate conserved DAMPs and PAMPs.…”
Section: Zinc-dependent Signaling In Neuronal Deathmentioning
confidence: 99%